PENGARUH NON-LINEAR SENTIMEN INVESTOR TERHADAP RETURN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2014-2015 - Fadhlillah Fadhillah; Faisal Faisal (Departemen Manajemen, 2017)
This research aims to understand the effect of psychological contract violation towards organizational citizenship behavior with depressive mood states as mediator variable. Empirical study on contract employees in Syiah Kuala University, Banda Aceh City. Sample in the research is 91 contract employees. The tool of data collecting used in this research is questionnaire, and sampling method is using proportional random sampling. the analysis data method is used in this research is HLM (Hierarchical Linear Modelling). The result of this research showing that psychological contract violation is negative towards organizational citizenship behavior, psychological contract violation is positive towards depressive mood states and depressive mood states is negative towards organizational citizenship behavior, also depressive mood states partially mediates the effect of psychological contract violation towards organizational citizenship behavior on contract employees in Syiah Kuala University.Keywords: Psychological Contract Violation, Organizational Citizenship Behavior, Depressive Mood States